Analisis Peran Dinas Pariwisata Kepemudaan dan Olahraga Kota Serang Dalam Pengembangan Wisata Religi Banten Lama (Berdasarkan Peraturan Daerah Kota Serang Nomor 14 Tahun 2014 Tentang Rencana Induk Pembangunan Kepariwisataan Daerah Tahun 2015-2025) - Annisa Ulya; Saifun Nufus; Fadhli Dzil Ikrom (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Tourism has an important role in development in a region and in a country. In line with the enactment of regional autonomy, giving authority to Regional Governments to make tourism development strategies to Regency/City regions to carry out regional tourism development and development. The regional government of Serang City is no exception, which has a strategy and continues to improve in developing religious tourism in the Old Banten. Researchers are interested in examining the role of the City of Serang Youth and Sports Tourism Office based on Serang City Regional Regulation Number 14 of 2014 concerning the Regional Tourism Development Master Plan for 2015- 2025 and what are the supporting and inhibiting factors in the development of Banten Lama religious tourism. The method used in this research is normative juridical and sociological juridical, with analytical descriptive research type. Collecting research data from secondary data which is the main data in the research, and primary data as a source of Youth and Sports Tourism in Serang City and qualitatively analyzed supporting data in the form of interviews with normative Office offices. The research results obtained were that the role of the Serang City Youth and Sports Tourism Office in the development of Banten Lama religious tourism had been carried out but was not yet optimal. Evidenced by the lack of optimal preservation of cultural heritage and other assets that have historical value, street vendors who are still selling in the mosque area, as well as less optimal arrangements for the flow of tourist visits. Supporting factors in the development of old Banten religious tourism are tourism potential which includes a strategic location as the capital city of Banten province, there are lands that have the potential to be developed as tourist destinations including religious tourism, as well as studies in the form of Detailed Engineering Design. the development of religious tourism in the Old Banten, namely the limitations of the Serang City Regional Budget, the lack of trained human resources in guiding tours in the Old Banten, and RIPPARDA which does not specifically regulate religious tourism.